International population census publication (Primary Source Microfilm, Gale Group, 2003)
Contains an introduction to the International Population Census Publications published by Primary Source Microfilm and a contents listing by reel to 50 reels of material containing statistical data for North America, Canada, 2001 and Mexico, 1990, 1995, 2000.